A genetic algorithm for the cryptanalysis of Chor-Rivest knapsack public key cryptosystem (PKC) - Taha, Imad; Sahasrabuddhe, H.V. (1999)
In this paper we develop a genetic algorithm as a method for cryptanalysing the Chor- Rivest knapsack PKC. As far as we know there is no feasible attack known on it [7]. The results show how the algorithm is effectively used to break this scheme by examining a very small fraction of the space of possible solutions. The algorithm found the exact solution in all attempted cases.